2019
DOI: 10.1111/lam.13153
|View full text |Cite
|
Sign up to set email alerts
|

Soil attributes in coal mining areas under recovery with bracatinga ( Mimosa scabrella )

Abstract: The coal reserves in the south of Brazil were intensely exploited at the time of great demand for such fuel. This resulted in changes in the environment, mainly in the chemical, physical and biological characteristics of the soil. Due to the potential to control erosive processes, increase soil quality and restore biological diversity, revegetation is a promising alternative to recover those impacted areas. In that respect, bracatinga is a pioneering tree species that easily grow in different environments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…For example, Xiao et al [54] have reported that soil microbial activity was affected by soil factors to different degrees, and that soil microbes played a critical role in the recycling of soil nutrients and soil fertility. Pille Da Silva et al [55] found that soil microbiological attributes affected microbial biomass carbon and microbial basal respiration. The microorganism could increase soil quality and restore biological diversity in the coal-mining area.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xiao et al [54] have reported that soil microbial activity was affected by soil factors to different degrees, and that soil microbes played a critical role in the recycling of soil nutrients and soil fertility. Pille Da Silva et al [55] found that soil microbiological attributes affected microbial biomass carbon and microbial basal respiration. The microorganism could increase soil quality and restore biological diversity in the coal-mining area.…”
Section: Discussionmentioning
confidence: 99%
“…A bracatinga é pouco exigente em relação às condições físicas e químicas do solo e, dessa forma, é amplamente utilizada em programas de recuperação de ambientes degradados (Silva et al, 2019). O principal uso da bracatinga é a madeira para geração de energia, porém é também utilizada na produção de celulose e painéis, além de apresentar potencial para uso ornamental, forrageiro, melífero e medicinal (Avrella et al, 2019).…”
Section: Introductionunclassified
“…Mimosa scabrella is a perennial plant and a facilitating species. It contributes in recovering degraded areas, minimizing in a few months the effects of weathering, avoiding the leaching and erosion processes and contributing to the incorporation of high levels of nitrogen and phosphorus (Saturno & Andrade, 2015;Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%